Statistical methods for trend detection and analysis in the environmental sciences - Chandler, R. E. (Richard E.); Scott, E. Marian; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2011)
"Statistical methodology itself has made some significant developments in areas that are highly relevant to the problems faced by environmentalists; thus this book fills a gap in the market in which there is currently a lot of interest. Split into two parts, part 1 - Theory and methods - introduces the basis for and scope of the book, and covers amongst others the chief topics of exploratory analysis, non-parametric estimation and testing, and parametric modeling. Part 2 - Case Studies - introduces a number of co-authors, specialists in their own areas of environmental science, to illustrate the application of the theory and methods in practice. The accompanying website develops the practical aspects raised in the book, and provides a useful complementary tool."--
Front Matter -- Methodology. Introduction -- Exploratory Analysis -- Parametric Modelling Deterministic Trends -- Nonparametric Trend Estimation -- Stochastic Trends -- Other Issues -- Case Studies. Additive Models for Sulphur Dioxide Pollution in Europe / Marco Giannitrapani, Adrian Bowman, E Marian Scott, Ron Smith -- Rainfall Trends in Southwest Western Australia / Richard E Chandler, Bryson C Bates, Stephen P Charles -- Estimation of Common Trends for Trophic Index Series / Alain F Zuur, Elena N Ieno, Cristina Mazziotti, Giuseppe Montanari, Attilio Rinaldi, Carla Rita Ferrari -- A SpaceTime Study on Forest Health / Thomas Kneib, Ludwig Fahrmeir -- Index -- Statistics in Practice.
Includes bibliographical references and index.
Electronic reproduction.
Text in English.
Keywords: Environmental sciences -- Statistical methods; MATHEMATICS -- Probability & Statistics -- General; Environmental sciences -- Statistical methods; Electronic books